1995
DOI: 10.1002/j.1460-2075.1995.tb07092.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo iodination of a misfolded proinsulin reveals co-localized signals for Bip binding and for degradation in the ER.

Abstract: The signal for degradation of proteins in the endoplasmic reticulum (ER) is thought to be the exposure of internal domains which are buried when the protein has adopted its correct conformation and which are also exposed in assembly intermediates. This raises the question of why the intermediates are not degraded. We developed a system based on the peroxidase‐catalyzed iodination of tyrosine residues which continuously monitors the exposure of internal domains of proinsulin. In CHO cells this system discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 46 publications
(25 reference statements)
1
30
0
Order By: Relevance
“…We show further that BiP is required to export p␣F from the ER and thus is involved in the recognition of ERAD substrates and/or directly in the export process. In support of this first hypothesis, other reports indicated that mammalian BiP recognizes aberrantly folded or unassembled polypeptides in the ER and targets them for degradation (24,34,35). A direct role for BiP in the export process is more difficult to imagine unless it regulates the translocation channel to permit access of ERAD substrates to the cytoplasm.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…We show further that BiP is required to export p␣F from the ER and thus is involved in the recognition of ERAD substrates and/or directly in the export process. In support of this first hypothesis, other reports indicated that mammalian BiP recognizes aberrantly folded or unassembled polypeptides in the ER and targets them for degradation (24,34,35). A direct role for BiP in the export process is more difficult to imagine unless it regulates the translocation channel to permit access of ERAD substrates to the cytoplasm.…”
Section: Discussionmentioning
confidence: 72%
“…Although the nature of this substrate selectivity is not completely clear, structural motifs that are buried when proteins are correctly folded and assembled may be recognized by the ERAD machinery if protein folding is hindered (22)(23)(24). Two ER lumenal molecular chaperones, BiP and calnexin, are known to be involved in protein maturation and "quality control" in the ER and are likely candidates to play a role in ERAD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with these hypotheses, several lines of evidence support a role for the lumenal Hsp70, BiP, in ERAD in both mammals and yeast. First, the proteolysis of ERAD substrates coincides with the rate at which they are released from BiP in the mammalian ER (Knittler et al, 1995;Beggah et al, 1996;Skowronek et al, 1998;Chillaron and Haas, 2000), and BiP associates preferentially with exposed regions of an unfolded ERAD substrate (Schmitz et al, 1995). Second, the degradation of an ERAD substrate is slowed when yeast contain a mutant allele in the gene encoding BiP, KAR2 (kar2-113;Plemper et al, 1997), and two ERAD substrates in yeast, CPY* and p␣F, aggregate in microsomes prepared from another kar2 mutant shifted to the nonpermissive temperature (kar2-203;Nishikawa et al, 2001).…”
mentioning
confidence: 99%
“…This might be a consequence of an increased number of functional stress protein molecules available for the formation of a complex with the substrate protein. Such an interaction may limit the exposure of a determinant(s) on the surface of the protein required for its targeting to degradation, as suggested by Schmitz et al (1995), resulting in the prolonged retention and stability of the substrate protein in the ER. …”
mentioning
confidence: 99%